2012
DOI: 10.1086/666082
|View full text |Cite
|
Sign up to set email alerts
|

Eviction and the Reproduction of Urban Poverty

Abstract: Combining statistical and ethnographic analyses, this article explores the prevalence and ramifications of eviction in the lives of the urban poor. A quantitative analysis of administrative and survey data finds that eviction is commonplace in inner-city black neighborhoods and that women from those neighborhoods are evicted at significantly higher rates than men. A qualitative analysis of ethnographic data based on fieldwork among evicted tenants and their landlords reveals multiple mechanisms propelling this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
339
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 500 publications
(367 citation statements)
references
References 54 publications
18
339
0
10
Order By: Relevance
“…In one study matching low income urban mothers who were evicted compared with those who were not evicted, mothers who were evicted were more likely to suffer depression, report worse health and more parenting stress (Desmond & Kimbro, 2015). As we know that housing instability is also likely to be accompanied by household instability, the effects are compounded (Desmond 2012).…”
Section: Health and Mobility Outcomesmentioning
confidence: 99%
“…In one study matching low income urban mothers who were evicted compared with those who were not evicted, mothers who were evicted were more likely to suffer depression, report worse health and more parenting stress (Desmond & Kimbro, 2015). As we know that housing instability is also likely to be accompanied by household instability, the effects are compounded (Desmond 2012).…”
Section: Health and Mobility Outcomesmentioning
confidence: 99%
“…Further details about all the variables can be found in table 3. A wide range of research has found mother's race/ethnicity to be an influence on residential mobility (Anderson 2012, p. 84;Coulton, Theodos, & Turner, 2009;Desmond 2012;Long 1992b, p. 866). As discussed in the literature review, maternal health is closely linked with child outcomes (Cicchetti, Rogosch, & Toth, 1998;Lyons-Ruth, Brofman & Parsons, 1999) and mobility (Anderson et al, 2014), which motivates our inclusion of these variables.…”
Section: Control Variablesmentioning
confidence: 99%
“…Involuntary moves theoretically could have damaging collateral effects on individuals. These moves could induce acute stress on parents from events such as eviction, which could in turn affect parenting and children's outcomes (Desmond 2012). Residential moves might also force children to change schools, which could potentially lower achievement for moving 22 students as well as students at receiving schools (Hanushek et al 2004).…”
Section: B Externalities From Housing Consumptionmentioning
confidence: 99%
“…Most renters sign annual lease agreements, which stipulate monthly payments of a fixed amount. Failure to meet agreed upon rental payments may lead to eviction, which in turn can lead to a spell of homelessness that in turn carries significant social cost (Desmond 2012). The only way to substantially reduce spending on housing is to move.…”
Section: Concentrating Vs Dispersing Subsidy Resourcesmentioning
confidence: 99%
See 1 more Smart Citation